The Faith-Based Digital Entrepreneurial Ecosystems: Integrating Institutional Logics, Digital Transformation, and Social Capital for Economic Empowerment in Indonesian Pesantren - Harjono Harjono; Yitno Puguh Martomo; Dion Candra Wardana; Bambang Supriadi (Universitas 17 Agustus 1945 Surabaya, 2026)
The study case is meant to explore the process of how pesantren (Islamic boarding school) in Indonesia can improve from conventional religious institution to produce economic empowerment by creating digitally supported entrepreneurial ecosystem. Drawing on institutional logics theory and digital transformation and entrepreneurial ecosystem research, this study develops a construct which informs the development of the Faith-Based Digital Entrepreneurial Ecosystem (FBDEE) model a framework aiming at an empirical validation. This exploratory research examines the interaction dynamics of the antecedents and consequences relationships between digital transformation, institutional capability as its pre-requisites based on survey data from many pesantren with their active business units. Another aspect is Social capital of the Islamic society also carve the behaviour forming ecosystem which design fundamentally economic empowerment. The results indicate digital transformation facilitates institutional capacity-building and correlates with direct enhancements to entrepreneurship ecosystem development. Institutional capability and Islamic social capital further facilitate ecosystem development opportunities, while the most significant predictors relating to economic empowerment (such income go generation; employment creation; sense of belonging to community) seem to be closely related with a democratisation process of an ecosystem formation. The mediation analysis shows that digital transformation works on economic empowerment mainly through the formation of ecosystems, whilst Islamic social capital positively moderates this mediator with digital transformation. As such, the study contributes theoretically to the literature by offering a novel theoretical perspective when integrating religious institutional logics with digital entrepreneurship and ecosystem frameworks in an emerging economy setting. It suggests that the interplay between digital modernization and what has been described as hybrid governance and trust-based networks is more complementary than diverging, such that this underpins a belief in particular faith–based institutional legitimacy. More concretely the findings provide policy relevant insight for capitalizing on pesantren as a couture-bound enabler of economically inclusive connectedness development meeting conducive ends in a grounded economic sense.